NEW THERMODYNAMIC MODEL OF THE STAUROLITE-GARNET GEOTHERMOMETER - Fed'kin V.V.; Aranovich L.Ya. (My University, 1989)
The staurolite-garnet geothermometer was first identified by Perchuk in an analysis of an empirical biotite-garnet geothermometer based on total chemical analyses of single-component fractions of coexisting biotite, garnet and staurolite from 13 staurolitic schist specimens. On the basis of revised understanding of thermodynamic parameters it has become possible to revise the Sta-Gr mineralogical geothermometer on the basis of the new data and to identify the properties of the Fe-Mg partition among minerals with correction for its nonideality and for the effect of third components (Ca in Gr, Zn in Sta, and Al and Ti in Bi. This new version of the Sta-Gr mineralogical geothermometer corrects for the nonideal character of the Fe-Mg interaction in staurolite and of the effect of Zn on the partitioning of iron and magnesium between staurolite and garnet. It accounts most effectively for the currently available data on the compositions of coexisting Sta and Gr with allowance for the thermodynamic properties of solid solutions of these phases.